Predicting coping with expectation violations: combining the ViolEx Model and the Covariation Principle - Pietzsch, Martin Christian; Pinquart, Martin (Frontiers in Psychology, 2023)
An experimental vignette study examined whether three specific situational cues predict ways of coping with violated expectations. The situational cues (consistency, distinctiveness, consensus) were derived from the Covariation Principle. The assessed coping strategies were based on the ViolEx Model—assimilation (activities to fulfill one’s expectation), accommodation (expectation change) and immunization (ignoring the discrepant information). A sample of 124 adults (mean age = 23.60 years; 49.19 percent psychology students) were randomly assigned to an experimental and control condition. Participants of the experimental condition read several vignettes about expectation violations with systematically manipulated situational cues, while participants of the control condition received the same vignettes without such cues. Participants had to rate the usefulness of each coping strategy per vignette. The situational cues mostly led to response shifts in coping tendencies: Situations with low consistency cues mostly led to immunization, whereas high consistency led to assimilation in the case of high distinctiveness and to accommodation in the case of low distinctiveness. Consensus cues only played a minor part in the coping process. The results show that situational characteristics influence people’s coping behavior, regardless of their dispositional preferences for certain coping strategies.